Secretome from hypoxic mesenchymal stem cells as a potential therapy for ischemic stroke: Investigations on VEGF and GFAP expression - Silvana, Sisca; Japardi, Iskandar; Rusda, Muhammad; Daulay, Rini S.; Putra, Agung; Mangunatmadja, Irawan; Darlan, Dewi M.; Sofyani, Sri; Andreas, Yana (Narra Sains Indonesia, 2024)
Ischemic stroke is a sudden onset of neurological deficit resulting from a blockage in cerebral blood vessels, which can lead to brain tissue damage, chronic disability, and increased risk of mortality. Secretome from hypoxic mesenchymal stem cells (SH-MSC) is a potential therapy to improve neurological deficit by increasing the expression of vascular endothelial growth factor (VEGF) and reducing glial fibrillary acidic protein (GFAP). These effects can reduce the infarction area of ischemic stroke. Therefore, the aim of this study was to analyze the effect of 150 μL and 300 μL SH-MSC injection on VEGF and GFAP expression as well as the improvement of infarction area in ischemic stroke animal model. A post-test-only experimental design with consecutive sampling was used, with Rattus norvegicus as subjects. Stromal mesenchymal stem cells (S-MSCs) were isolated from the umbilical cords of rats at 21 days of gestation. Secretome production by the S-MSCs was induced under a hypoxic condition, and subsequently isolated. The resultant secretome was administered to rats subjected to middle cerebral artery occlusion (MCAO) at doses of 150 μL (P1 group) and 300 μL (P2 group). The results showed that the infarction area was reduced in P1 (p<0.001) and P2 groups (p<0.001). SH-MSC at a dose of 300 μL increased the expression of VEGF (p=0.028) and reduced the expression of GFAP (p=0.001). In conclusion, secretome from hypoxic S-MSC could potentially improve ischemic stroke by upregulating VEGF expression and downregulating GFAP expression.